GEW-Handbuch Promovieren mit Perspektive Ein Ratgeber von und für DoktorandInnen - Günauer, Franziska; Krüger, Anne K.; Moes, Johannes; Steidten, Torsten (GEW-Materialien aus Hochschule und Forschung, 2012)
The extensively updated reprint of the handbook "Doctorate with prospects" is aimed at all those who are planning or are already in the middle of doctoral studies. The guidebook includes considerable information about relevant aspects of doctoral studies: * Writing an exposé * Financing the doctoral studies * Issues relating to the Social Law * Support provisions and structured doctoral studies models and stays abroad * Professional prospects of future doctoral students. In addition to the material and social aspects the team of authors also deals with the organisation of graduate schools as part of the initiative of excellence of the federal government and states. The handbook is the perfect source of information for doctoral students, but also for Universities and the public dealing with providing advice and financing of doctoral studies. Die umfassend aktualisierte Neuauflage des Handbuchs "Promovieren mit Perspektive" wendet sich an alle, die eine Promotion planen oder bereits durchführen.Der Ratgeber enthält umfangreiche Informationen zu relevanten Aspekten des Promovierens: * Verfassen des Exposés * Finanzierung der Promotion * sozialrechtliche Fragestellungen * Unterstützungsangebote und strukturierte Promotionsmodelle und Auslandsaufenthalte * berufliche Perspektiven angehender DoktorandInnen. Neben den materiellen und sozialen Aspekten setzen sich das Autorenteam auch mit dem Aufbau von Graduiertenschulen in der Exzellenzinitiative von Bund und Ländern auseinander